2023
DOI: 10.3389/fnagi.2023.1258979
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and aspiration during a Parkinson's hospitalization: a care partner's perspective and recommendations for improving standards of care

Annie Brooks

Abstract: People with Parkinson's disease have a significantly increased incidence and risk of aspiration pneumonia when compared to those without. Aspiration pneumonia associated with dysphagia (swallowing issues), which is the leading cause of death among people with Parkinson's disease, accounting for 25% of Parkinson's deaths. There is relatively limited evidence of the most effective strategies to balance the competing needs of each Parkinson's patient as providers aim to prevent, diagnose, and manage dysphagia. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is also important to note that none of the studies analyzed in this review compared hospitalization results for those patients admitted post-operatively to hospitals that perform DBS and thus likely have more experience with patient populations with PD vs. those admitted to community hospitals without such dedicated resources. Many articles, both within this special issue and elsewhere, have noted that some hospitals may be inexperienced with PD-specific aspects of care, such as the importance of medication timing, the screening and management of dysphagia to reduce incidence of aspiration pneumonia, ensuring sufficient exercise to maintain motor abilities without allowing increased falls, and avoiding contra-indicated medications (Palmer et al, 2021;Brooks, 2023;Goldin et al, 2023;Shurer et al, 2023). It is unclear if perhaps having DBS may even improve outcomes in small community hospitals where there may be less awareness regarding medication timing and access in PD, both of which are known 10.3389/fnagi.2023.1258190 risks for prolonged hospitalization in PD patients.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…It is also important to note that none of the studies analyzed in this review compared hospitalization results for those patients admitted post-operatively to hospitals that perform DBS and thus likely have more experience with patient populations with PD vs. those admitted to community hospitals without such dedicated resources. Many articles, both within this special issue and elsewhere, have noted that some hospitals may be inexperienced with PD-specific aspects of care, such as the importance of medication timing, the screening and management of dysphagia to reduce incidence of aspiration pneumonia, ensuring sufficient exercise to maintain motor abilities without allowing increased falls, and avoiding contra-indicated medications (Palmer et al, 2021;Brooks, 2023;Goldin et al, 2023;Shurer et al, 2023). It is unclear if perhaps having DBS may even improve outcomes in small community hospitals where there may be less awareness regarding medication timing and access in PD, both of which are known 10.3389/fnagi.2023.1258190 risks for prolonged hospitalization in PD patients.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…A literature review revealed that pharmacological options for addressing this issue are limited and, in many cases, only partially effective, leaving a critical unmet need in the management of this condition. The reported high rates of aspiration of thin fluids and subsequent development of aspiration pneumonia, a common cause of death in individuals with PD, also provide further evidence that the current approach to dysphagia management is still inadequate, and is reported to be unsatisfactory by those affected by PD, carers, and healthcare professionals 6 , 9 , 10 . Swallowing therapy is recognised as a core element in the treatment of dysphagia in PD, comprising standard swallowing therapy, the use of liquid thickeners, posture strategies, skill-based therapy, Lee Silverman Voice Therapy, and electrical muscle stimulation.…”
Section: Introductionmentioning
confidence: 98%